1995
DOI: 10.1016/0190-9622(95)90060-8
|View full text |Cite
|
Sign up to set email alerts
|

Lichen sclerosus

Abstract: Lichen sclerosus, usually appearing in the dermatologic literature under the names of lichen sclerosus et atrophicus, balanitis xerotica obliterans, and kraurosis vulvae, is an inflammatory disease with a multifactorial origin. A past association of lichen sclerosus and genital squamous cell carcinoma is not as close as once thought. Once considered primarily a surgical problem, especially when the genitals were involved, lichen sclerosus will respond to a variety of systemic and topical therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
352
3
24

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 347 publications
(394 citation statements)
references
References 224 publications
10
352
3
24
Order By: Relevance
“…With sequential biopsies, several investigators have reported transition from LSA to morphea or vice versa 10,11 . However, other investigators believe there are enough clinical and histologic differences between LSA and morphea to argue that they are distict diseases and that coexistent lesions are coincidental 1 . It is possible that this LSA case could progress to en coup de Sabre, and this case may be a transitional form of linear scleroderma en coup de Sabre 5 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With sequential biopsies, several investigators have reported transition from LSA to morphea or vice versa 10,11 . However, other investigators believe there are enough clinical and histologic differences between LSA and morphea to argue that they are distict diseases and that coexistent lesions are coincidental 1 . It is possible that this LSA case could progress to en coup de Sabre, and this case may be a transitional form of linear scleroderma en coup de Sabre 5 .…”
Section: Discussionmentioning
confidence: 99%
“…However, extragenital LSA is not uncommon and it was found in 805 of 5,207 cases reviewed by Meffert et al 1 and it was most common on the neck, shoulders and upper portion of the trunk. It is generally asymptomatic, but it can occasionally be pruritic.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…呕adne z dotychczas przeprowadzonych bada艅 nie wyja艣ni艂o jednoznacznie mechanizmu prowadz膮cego do rozwoju tej jednostki chorobowej. W艣r贸d teorii dotycz膮cych patomechanizmu wymienia si臋: teori臋 autoimmunologiczn膮, wp艂yw czynnik贸w genetycznych, infekcje, czynniki dzia艂aj膮ce miejscowo oraz udzia艂 hormon贸w [5,6]. Obecno艣膰 pewnych haplotyp贸w ludzkich antygen贸w leukocytarnych (human leukocyte antigens -HLA) chroni przed pojawieniem si臋 LS sromu, natomiast ekspresja innych haplotyp贸w jest silniej wyra偶ona, je艣li choroba pojawia si臋 ju偶 w dzieci艅stwie [7].…”
Section: Wst臋punclassified
“…Lichen sclerosus is a chronic inflammatory skin disorder of unknown aetiology in which genetic, physiological and environmental factors may all contribute to susceptibility, clinical phenotype and outcome of the disease [40][41][42]. Patients are characterised by white indurated papules and plaques often with ecchymosis that most commonly affect the genitalia (85% to 98% of the cases).…”
Section: Ecm1 and Lichen Sclerosusmentioning
confidence: 99%